Minor physical anomalies and craniofacial measures in patients with treatment-resistant schizophrenia. Issue 9 (17th December 2014) - Lin, A.-S.; Chang, S.-S.; Lin, S.-H.; Peng, Y.-C.; Hwu, H.-G.; Chen, W. J.
Abstract : Background: Schizophrenia patients have higher rates of minor physical anomalies (MPAs) than controls, particularly in the craniofacial region; this difference lends support to the neurodevelopmental model of schizophrenia. Whether MPAs are associated with treatment response in schizophrenia remains unknown. The aim of this case–control study was to investigate whether more MPAs and specific quantitative craniofacial features in patients with schizophrenia are associated with operationally defined treatment resistance. Method: A comprehensive scale, consisting of both qualitatively measured MPAs and quantitative measurements of the head and face, was applied in 108 patients with treatment-resistant schizophrenia (TRS) and in 104 non-TRS patients. Treatment resistance was determined according to the criteria proposed by Conley & Kelly (2001; Biological Psychiatry 50, 898–911). Results: Our results revealed that patients with TRS had higher MPA scores in the mouth region than non-TRS patients, and the two groups also differed in four quantitative measurements (facial width, lower facial height, facial height, and length of the philtrum), after controlling for multiple comparisons using the false discovery rate. Among these dysmorphological measurements, three MPA item types (mouth MPA score, facial width, and lower facial height) and earlier disease onset were further demonstrated to have good discriminant validity in distinguishing TRS from non-TRS patients in a multivariable logistic regression analysis, with an area under the curve of 0.84 and a generalized R 2 of 0.32. Conclusions: These findings suggest that certain MPAs and craniofacial features may serve as useful markers for identifying TRS at early stages of the illness.